2016
DOI: 10.1039/c6dt02698b
|View full text |Cite
|
Sign up to set email alerts
|

Ligand coordination modulates reductive elimination from aluminium(iii)

Abstract: Oxidative addition of inert bonds at low-valent main-group centres is becoming a major class of reactivity for these species. The reverse reaction, reductive elimination, is possible in some cases but far rarer. Here, we present a mechanistic study of reductive elimination from Al(iii) centres and unravel ligand effects in this process. Experimentally determined activation and thermodynamic parameters for the reductive elimination of Cp*H from Cp*2AlH are reported, and this reaction is found to be inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…[14] Similar,S chnçck-elsC p*Al [15] has been shown to undergo reversible OA/RE with the activated diene C À Hb ond in Cp*H giving Cp* 2 AlH. [16] Similar to this reactivity,C rimmin described cleavage of the activated allylic CÀHb ond in propene by ( DIPP BDI)Al in benzene (80 8 8C, 14 h). [17] Reaction of ad ialumene with PhCCH also resulted in CÀHa ctivation (Sche-me 2c), apart from [2+ +2]-cycloaddition.…”
Section: Introductionmentioning
confidence: 85%
“…[14] Similar,S chnçck-elsC p*Al [15] has been shown to undergo reversible OA/RE with the activated diene C À Hb ond in Cp*H giving Cp* 2 AlH. [16] Similar to this reactivity,C rimmin described cleavage of the activated allylic CÀHb ond in propene by ( DIPP BDI)Al in benzene (80 8 8C, 14 h). [17] Reaction of ad ialumene with PhCCH also resulted in CÀHa ctivation (Sche-me 2c), apart from [2+ +2]-cycloaddition.…”
Section: Introductionmentioning
confidence: 85%
“…[14] Similar,S chnçk-kelsCp*Al [15] has been shown to undergo reversible OA/RE with the activated diene C À Hb ond in Cp*H giving Cp* 2 AlH. [16] Similar to this reactivity,C rimmin described cleavage of the activated allylic C À Hb ond in propene by ( DIPP BDI)Al in benzene (80 8 8C, 14 h). [17] Reaction of ad ialumene with PhCCH also resulted in CÀHa ctivation (Scheme 2c), apart from [2+ +2]-cycloaddition.…”
Section: Introductionmentioning
confidence: 87%
“…Fischer and co‐workers reported the reductive elimination of Cp*H from Cp*AlH 2 to yield the reactive [Cp*Al] 4 species . Further study by Cowley and co‐workers reported the effect of coordinated ligands on the promotion of this reductive elimination step and found that increasing coordination number and electron density at the Al(III) centre inhibits reductive elimination . In related work, by Braunschweig and co‐workers showed that Lewis bases were capable of mediating the Al(II) to Al(I)/Al(III) disproportionation .…”
Section: Reductive Eliminationmentioning
confidence: 99%